(untitled) (Journal of Economic Research & Business Administration, 2016)
As the domestic and foreign experience, the crisis in the country in general and energy in particular, adversely affect such an important indicator of the energy efficiency of electricity transmission and distribution, as her loss in electric grids. Due to the sharp decline in investment in the development and modernization of electric grids, the improvement of management systems of their regimes, electricity metering, there was a number of negative trends negatively affecting the level of losses in the electric grids. For example, the outdated equipment, physical and moral deterioration of the accounting system of electricity transmission capacity mismatch installed hardware. This article discusses the value arising from the transfer of losses of electricity. The article also examines the impact of the formation and dynamics of these losses on the cost of the electricity tariff.